Classifying the metal dependence of uncharacterized nitrogenases - Mcglynn, Shawn E.; Boyd, Eric S.; Peters, John W.; Orphan, Victoria J. (Frontiers in Microbiology, 2013)
Nitrogenase enzymes have evolved complex iron-sulfur (Fe-S) containing cofactors that most commonly contain molybdenum (MoFe, Nif) as a heterometal but also exist as vanadium (VFe, Vnf) and heterometal independent (Fe-only, Anf) forms. All three varieties are capable of the reduction of dinitrogen (N2) to ammonia (NH3) but exhibit differences in catalytic rates and substrate specificity unique to metal type. Recently, N2 reduction activity was observed in archaeal methanotrophs and methanogens that encode for nitrogenase homologs which do not cluster phylogenetically with previously characterized nitrogenases. To gain insight into the metal cofactors of these uncharacterized nitrogenase homologs, predicted three-dimensional structures of the nitrogenase active site metal-cofactor binding subunits NifD, VnfD, and AnfD were generated and compared. Dendograms based on structural similarity indicate nitrogenase homologs cluster based on heterometal content and that uncharacterized nitrogenase D homologs cluster with NifD, providing evidence that the structure of the enzyme has evolved in response to metal utilization. Characterization of the structural environment of the nitrogenase active site revealed amino acid variations that are unique to each class of nitrogenase as defined by heterometal cofactor content; uncharacterized nitrogenases contain amino acids near the active site most similar to NifD. Together, these results suggest that uncharacterized nitrogenase homologs present in numerous anaerobic methanogens, archaeal methanotrophs, and firmicutes bind FeMo-co in their active site, and add to growing evidence that diversification of metal utilization likely occurred in an anaerobic habitat.